Odpowiedzi

2010-04-07T18:31:28+02:00
3x=2y
x=-25+y

3(-25+y)=2y
x=-25+y

-75+3y=2y
x=-25+y

-75=2y-3y
x=-25+y

-75=-y
x=-25+y

y=75
x=-25+75

y=75
x=50


2.
{ x/5 - y/4 = 0 *20
x/2 - y/16 = 5,5 *16

4x-5y=0 *-2
8x-y=88

-8x+20y=0
8x-y=88

22y=88
y=4

-8x+20y=0
-8x+20*4=0
-8x+80=0
-8x=-80
-x=-10
x=10

odp. x=10, y=4



2010-04-07T18:31:42+02:00
X/2 = y/3 |*6
{
x+ 2,5= y

x/2*6=6*y/3
{
x-y=-2,5

3x=2y
{
x-y=-2,5

3x-2y=0
{
x-y=-2,5 |*(-3)

3x-2y=0 trzeba skreślić 3x i (-3x)
-3x+3y=7,5

y=7,5

3x=2y
3x=2*7,5
3x=15 |:3
x=5

2 5 2
2010-04-07T18:40:15+02:00
{ x/2 = y/3
x+ 2,5= y

3x=2y
x-y=-2,5


3x-2y=0
x=-2,5+y

3(-2,5+y)-2y=0
x=-2,5+y

-7,5+3y-2y=0
x=-2,5+y

y=7,5
x=-2,5+7,5

y=7,5
x=5

x=5
y=7,5

------------
{x/5 - y/4 = 0 * 20
x/2 - y/16 = 5,5*16

4x-5y=0* (-2) to wyszlo przez pomnozenie liczb przez 20
8x-y=88 to wyszlo przez pomnozenie liczb przez 16

-8x+10y=0
8x-1y=88

9y=88/9
y=9 i 7/9

4x-5* 9 i 7/9 =0
y=9 i 7/9

4x=88/9 : 4
y=9 i 7/9

x=2 i 4/9
y=9 i 7/9